MIMO radar signals with better correlation characteristics - Bezoušek, Pavel; Karamazov, Simeon (Slovenská technická univezita v Bratislave, 2020)
MIMO radars employ multiple transmitting and receiving antennae. For each transmitting antenna, an independent and easily distinguishable signal is required, and appropriate filters must be used by the receiver. For this, the transmitted signals should have characteristics, enabling their effective separation. In this paper the correlation characteristics of selected signals are compared, and the appropriate signal coding is suggested. For differentiation, we address signals with basic linear or nonlinear frequency modulation (LFM or NLFM) multiplied by Gold, PRN, or frequency diversity (FD) codes. The analysis shows that better signal characteristics are achieved using the FD than the other codes. Using matched filters with filter length of 511, sidelobes and cross-correlations are suppressed by 40 dB with FD codes, while with the other codes only 20 dB was achieved. It was also proven, that the FD codes are more tolerant to the Doppler shift. On the other hand, the FD codes application leads to an extension of the overall transmitted signal bandwidth. This however, only represents a serious barrier for very broadband radar systems.
Radarové signály MIMO s lepšími korelačními charakteristikam
Keywords: MIMO radar; autocorrelation function; time-frequency cross correlation; matched filter; frequency modulation; gold codes; MIMO radar; autokorelační funkce